Aerodynamics optimization of rear car - Mohd Nazirul Mubin, Mohammad Zaki (2008)
Automotive aerodynamic is the study of air flow characteristic around and through a vehicle during motion. In this project, a flow characteristic study is including pressure distribution on the car concentrating only at rear body. For any current car that has received aerodynamic attention, the contribution of the fore body to drag is usually small. The objectives of this project are to estimate the drag and find the optimization of rear shape of body at constant velocity 110 km/h by using aerodynamic simulation software that is Computational Fluid Dynamic (CFD). From the analysis by CFD, the force value is created as goal and from force value; drag coefficient can be estimated by using a mathematical equation. Before the analysis can performed, a geometrical model with different shape of the rear body must be created first by using Computer Aided Design software (CAD). By using design and shape variation by means of multiple rear slant angle and rear bonnet, analysis was done in CFD. From the data, coefficient of drag, CD was calculated for every shape and in order to get the optimization shape, the shape that has lowest value of CD was combined in a one model and then the model was simulate again in CFD. After simulation was done, the result gives the lowest value of CD and the objective to find the optimization of rear shape was successful achieved.